Transformações estruturais em uma topossequência sobre basaltos em Maruinbi-PR - Fumiya, Marcel Hideyuki (2013)
The knowledge of the organization and autochthonous or allochthonous origin of the material which composes the soil, especially in aspects of slope scale, provides tools to evaluate the ways in which it gives relief evolution and the profile alterations along the slope. The study of the soil physical, chemical, mineragical properties along of the toposequence allows us to understand the dynamics of pedogenic processes, assisting in understanding the evolution of the soil. In this research were identified the following soil types Nitossolo - Nitosol latosolic - Cambisol - Nitosol from upstream to downstream. The analysis of micromorphological thin sections of soil, indicate that the structural transformation is occurring in the blocks structure (typical of nitic B horizon) to micro-aggregate or granular structure (typical latosolic B horizon) from the fragmentation processes. In the trenches along the toposequence there was also the presence of detrital paleo paviment "stone lines" which are records of an intense performance of morphogenesis in semi-arid climate in the region. This process is responsible for sculpturing and modeling of the shape of the current relief. The study area is located in the watershed of Água do Sete stream in Marumbi - PR, at Terceiro Planalto Paranaense. The watershed sits on rocks of the Serra Geral Formation, cropped by diabase dykes of Cretaceous age. The toposequence studied has 730m long, featured by levels caused by difference in lithologic resistance.